Prospective on publishing negative results (Journal of Pharmaceutical Negative Results, 2015)
Publication is an usual practice among researchers postcompletion of any research project or investigation.Publication is also a kind of documentation Process,which originated in the Neolithic human period itself.Documentation has been an ever-preset even sinceNeolithic times through the modus operandi is varied.[1]